IMPACT OF DEMOGRAPHIC VARIABLES ON THE CUSTOMERS’ CHOICE OF DIFFERENT MODES OF BANKING TRANSACTIONS IN ODISHA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
The customers have several options to carry out  their banking transactions. They can either go to  branch to carry out their transactions, use their  ATM debit card, use their credit card or internet  banking, mobile banking etc. This study aimed  to study the impact of demographic variables  of the customers on their choice of different  modes of banking transactions and also their  preferred mode of transaction. For this purpose  a questionnaire was developed and distributed to  400 customers from private banks in Cuttack,  Bhubaneswar and Rourkela out of which 291  were completed and returned yielding a response  rate of 72.8%. In this research the impact of  four demographic variables was studied, they are  gender, age, occupation and income. The modes  of banking transactions which were selected  in this study are branch, ATM card, credit  card, internet banking and mobile banking.  The responses obtained were analysed using  t-test and one way ANOVA. In this study it is  observed that in case of demographic variable  ‘gender’ it was only in case of usage of credit  card for bank transaction where there is no  significant difference regarding the opinions of  male and female respondents. In the case of the  demographic variable ‘occupation’ it was only  in case of ATM card transactions, there is no  significant difference regarding the opinions  of the respondents from various occupational  backgrounds. ATM was found to be the most  preferred mode of banking transaction by  the respondents so the intervention of bank  employees are required so that the transaction  through other modes like internet banking,  credit card and mobile banking could be  increased.
Keywords: Demographic variables,; Banking transactions; t-test; One way ANOVA